Community-based interventional study for tobacco cessation in urban slums of Ahmedabad City: A cluster-randomized trial - Anjali Mall; Sheetal Vyas (Indian Journal of Community Medicine, 2021)
Background: Tobacco is one of the most important preventable causes of death and a leading public health problem all over the world. The present study was conducted to determine the effect of community-based intervention for tobacco cessation in urban slums of Ahmedabad city. Materials and Methods: A total of 20 slums (10 slums each) in the intervention and control group were randomly selected through the process of randomization. A total of 200 participants each in the intervention and control group were studied through a cluster-randomized trial. Results: The outcome of the community-based tobacco intervention measured after 6 months depicted that the odds ratio (OR) of the prevalence of tobacco abstinence, quit rate, and reduction of more than 50% of tobacco use was significantly higher (30.37 times, 2.84 times, and 2.19 times respectively more) in the intervention as compared to the control group. However, after 1 year of the first and immediately after the second intervention, the OR of tobacco point prevalence abstinence, quit rate, and reduction of more than 50% was more pronounced (5.11 times, 3.52 times, and 4.31 times, respectively, more) in the intervention group than the control group. Post intervention, it was also observed that there was a significant increase in the average quit attempt. Conclusion: The community-based intervention was very effective in reducing the consumption of tobacco in urban slums in any form. As per the study findings, there is a wide possibility for the integration of tobacco cessation activity into the health program.